2002
DOI: 10.1085/jgp.119.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Two Temporal Phases of Light Adaptation in Retinal Rods

Abstract: Vertebrate rod photoreceptors adjust their sensitivity as they adapt during exposure to steady light. Light adaptation prevents the rod from saturating and significantly extends its dynamic range. We examined the time course of the onset of light adaptation in bullfrog rods and compared it with the projected onset of feedback reactions thought to underlie light adaptation on the molecular level. We found that adaptation developed in two distinct temporal phases: (1) a fast phase that operated within seconds af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
62
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 76 publications
5
62
0
Order By: Relevance
“…Although phototransduction has been studied extensively, there are still unknown factors that influence the timing and amplification of signaling under conditions of sustained illumination (26,27). Previously, we showed that recombinant GRK1 can be phosphorylated in retina extracts by an endogenous kinase (12).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although phototransduction has been studied extensively, there are still unknown factors that influence the timing and amplification of signaling under conditions of sustained illumination (26,27). Previously, we showed that recombinant GRK1 can be phosphorylated in retina extracts by an endogenous kinase (12).…”
Section: Resultsmentioning
confidence: 99%
“…Several groups have attempted to characterize the various factors responsible for light adaptation and determined that different mechanisms might be functioning during distinct phases of adaptation. For example, Calvert et al (26) noted two phases of adaptation: the better characterized fast phase with a time constant of 1-2 s, and a slower phase observed only at high light intensities. Burns and co-workers also identified a novel mechanism of adaptation, known as adaptive acceleration, which accelerates recovery and persists for many seconds (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrophysiological evidence supports the hypothesis that factors in addition to transducin deactivation are involved in regulating the lifetime of light-activated PDE6 during light adaptation of rod photoreceptors (5,6). Several potential feedback mechanisms for modulating activated PDE6 have been proposed (7-9) but have not been explored in sufficient detail to validate their relevance to the phototransduction pathway.…”
mentioning
confidence: 82%
“…All of these domains have been found to participate in the regulation of GAP activity and substrate specificity (9 -11). The inhibitory PDE␥ subunit of the effector regulated by G␣ t , cGMP phosphodiesterase (PDE6), interacts with both G␣ t and the catalytic core of RGS9-1 and enhances RGS9-1 GAP activity (12)(13)(14) in vitro, but it is not clear how this enhancement is accomplished in a physiological setting in which tight PDE␥ binding to PDE6 catalytic subunits blocks GAP enhancement (15)(16)(17)(18).…”
mentioning
confidence: 99%